Performance and economics of replanted cardamom (Elettaria cardamomum Maton) plantation - Korikanthimath, V S (Journal of Spices and Aromatic Crops, 2000)
The performance and economics of replanting of cardamom (Elettaria cardamomum) was studied at Chettalli (Kodagu District, Karnataka, India). An average yield of 749 kg (dry)/ha of cardamom was obtained for five crop seasons which was 5.35 times higher than the national average yield of 140 kg/ha. A highest yield of 1775 kg/ha (dry) was recorded during the second year after replanting. Out of 869.8 labour days required per ha per year during the bearing period, the requirement of women labourers was higher (87.4%); 57.8% labour requirement was for picking only. Maximum expenses (69.45%; Rs. 57,230.80/ha) was incurred on labour charges. A net income of Rs. 1,96,986.20/ha (average of five crop seasons) was obtained with a production cost of Rs. 130.97/kg (dry). The discounting cash flow measures namely, Net Present Value (NPV) of Rs. 5,09,296.45, Benefit Cost Ratio (BCR) of 2.78 and Pay Back Period (PBP) of 2.15 years indicated that replanting of cardamom is an economically viable and financially feasible proposition.